Genetic variation in the NBS1, MRE11, RAD50 and BLM genes and susceptibility to non-Hodgkin lymphoma - Gascoyne Randy D; Connors Joseph M; Gallagher Richard P; Lai Agnes S; Leach Stephen; MacArthur Amy C; Schuetz Johanna M; Spinelli John J; Brooks-Wilson Angela R (BMC, 2009)
Abstract Background Translocations are hallmarks of non-Hodgkin lymphoma (NHL) genomes. Because lymphoid cell development processes require the creation and repair of double stranded breaks, it is not surprising that disruption of this type of DNA repair can cause cancer. The members of the MRE11-RAD50-NBS1 (MRN) complex and BLM have central roles in maintenance of DNA integrity. Severe mutations in any of these genes cause genetic disorders, some of which are characterized by increased risk of lymphoma. Methods We surveyed the genetic variation in these genes in constitutional DNA of NHL patients by means of gene re-sequencing, then conducted genetic association tests for susceptibility to NHL in a population-based collection of 797 NHL cases and 793 controls. Results 114 SNPs were discovered in our sequenced samples, 61% of which were novel and not previously reported in dbSNP. Although four variants, two in RAD50 and two in NBS1, showed association results suggestive of an effect on NHL, they were not significant after correction for multiple tests. Conclusion These results suggest an influence of RAD50 and NBS1 on susceptibility to diffuse large B-cell lymphoma and marginal zone lymphoma. Larger association and functional studies could confirm such a role.